(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Shepelenko T. L. Formation of professionally mobile personality of the future specialist in economics. The article deals with the essence of professional mobility, defined as a mobile professional individual student. The article explores the pedagogical conditions for efficient formation of professional mobility in future economists.